Entre telescópios e potes de barro: O eclipse solar e as expedições científicas em 1919/Sobral-CE - Rodrigues, Joyce Mota (2012)
This research seeks to understand the daily routine of British, American and Brazilian Expeditions, in 1919, in the city of Sobral, in an attempt to confirm the Theory of Relativity by Albert Einstein. The relationships developed between scientists, local authorities and the media expose the discourses and scientific practices of modernity and backwardness local.